Correction: Citizen Science Terminology Matters: Exploring Key Terms. (22nd June 2017) - Eitzel, M V; Cappadonna, Jessica L; Santos-Lang, Chris; Duerr, Ruth Ellen; Virapongse, Arika; West, Sarah Elizabeth; Kyba, Christopher Conrad Maximillian; Bowser, Anne; Cooper, Caren Beth; Sforzi, Andrea; Metcalfe, Anya Nova; Harris, Edward S; et al.
This article details a correction to the article: Eitzel, M V, et al. (2017 ). Citizen Science Terminology Matters: Exploring Key Terms. Citizen Science: Theory and Practice, 2(1), p. 1. DOI:https://doi.org/10.5334/cstp.96